ECO-FRIENDLY SYNTHESIS OF CARBON NANOPARTICLES USING TERMINALIA CATAPPA SEED OIL: EVALUATION OF ANTICANCER ACTIVITY IN LUNG CANCER (International Journal of Food and Nutritional Sciences, 2023)
Recent developments in nanobiotechnology have positioned it as an important approach for present-day disease diagnosis and therapy. In this work, oil extracted from the seeds of T. catappa was processed through thermal decomposition to obtain carbon nanoparticles (CNPs). The synthesized particles were verified and studied using multiple analytical techniques, including UV–Vis spectroscopy, FT-IR, scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray diffraction (XRD). The anticancer potential of the CNPs was evaluated against the A549 human lung cancer cell line. The half-maximal inhibitory concentration (IC₅₀) was determined to be 148.193 ± 3.099 µg/mL, indicating a moderate level of cytotoxicity. These findings suggest that carbon nanoparticles derived from T. catappa seeds may hold promise as a supportive strategy in lung cancer therapy. Furthermore, this study summarizes current progress in the field and highlights the potential of such plant-based CNPs for future anticancer drug development.